Do Independent Directors Tell the Truth, the Whole Truth, and Nothing but the Truth When They Resign?. (January 2021) - Bar-Hava, Keren; Huang, Sterling; Segal, Benjamin; Segal, Dan
We examine the informativeness and credibility of independent directors' stated resignation reasons. We posit that having access to private information, directors may resign in anticipation of weak future underperformance to limit damage to their reputation and further have an incentive to mask the reason for the resignation. Results show likelihood of resignation increases with director's reputation and weak future firm performance. In addition, the evidence is consistent with directors obfuscating the reason for departure by providing benign and unverifiable resignation reasons. Investors seem aware of the disclosure incentives of departing directors and react negatively to such resignations. However, investors, by and large, underreact to the resignation announcement, likely because of the benign reason given for the resignation. Our results suggest that notwithstanding the perception of outside directors' impartiality and assumed interest alignment with shareholders, independent directors' personal reputation concerns may conflict with the interests of shareholders to whom they owe fiduciary duties.